Optogenetic manipulation of cardiac electrical dynamics using sub-threshold illumination: dissecting the role of cardiac alternans in terminating rapid rhythms. (10th June 2022) - Biasci, V; Santini, L; Hussaini, S; Ferrantini, C; Coppini, R; Loew, LM; Luther, S; Campione, M; Poggesi, C; Pavone, FS; Cerbai, E; Bub, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Cardiac action potential (AP) shape and propagation are regulated by several key dynamic factors such as ions channel recovery and intracellular Ca2+-cycling. Experimental methods for manipulating AP electrical dynamics commonly use ion channel inhibitors that lack spatial and temporal specificity. In this work, we propose a novel approach based on optogenetics to manipulate cardiac electrical activity employing a light-modulated depolarizing current with intensities that are too low to elicit APs (sub-threshold illumination) but are sufficient to fine-tune AP electrical dynamics. We investigated the effects of sub-threshold illumination in isolated cardiomyocytes and whole hearts by using transgenic mice constitutively expressing a light-gated ion channel (channelrhodopsins-2, ChR2). We find that ChR2-mediated depolarizing current prolongs APs and reduces conduction velocity (CV) in a space-selective and reversible manner. Sub-threshold manipulation also affects the dynamics of cardiac electrical activity, increasing the magnitude of cardiac alternans. We use an optical system that uses real-time feedback control to generate re-entrant circuits with user-defined cycle lengths to explore the role that cardiac alternans plays in spontaneous termination of ventricular tachycardias (VTs). We find that VT stability significantly decreases during sub-threshold illumination primarily due to an increase in the amplitude of electrical oscillations, which implies that cardiac alternans may be beneficial in the context of self-termination of VT.